Graphite carbon nitride doped with a benzene ring for enhanced photocatalytic H2 evolution. Issue 24 (24th February 2021) - Yuan, Hai Yang; Bai, Jing Yang; Xu, Beibei; Li, Xin Yan; Xiao, Shi Yang; Liu, Peng Fei; Wang, Xue Lu; Yang, Hua Gui
Abstract : g-C3 N4 doped with a benzene ring was synthesized by one-step polycondensation, exhibiting accelerated charge separation and transfer abilities. Abstract : Graphitic carbon nitride (g-C3 N4 ) has been identified as a promising material for photocatalytic hydrogen (H2 ) production, but it shows a low activity. Herein, g-C3 N4 doped with a benzene ring (B–CN x ) was synthesized via a simple thermal polycondensation method, exhibits 5.4 times higher H2 evolution rate than the pristine one, and achieves a high apparent quantum yield of 4.11% at 420 nm.